MENAKAR KETERHUBUNGAN IPM DAN TINGKAT KEMISKINAN DI PROVINSI ACEH - Prayudi Setiawan Prabowo (Syiah Kuala University, 2020)
Abstract This study aims to see the causality between the Human Development Index (HDI) and the Poverty Level in Aceh Province. Where to identify whether HDI has an effect on the poverty level or the poverty level which affects HDI more. This study uses Granger Causality analysis and PVAR Modeling to find answers to the research objectives. As well as using regional Panel data for a period of 2015 to 2019. The results show that there is a causal relationship between HDI and poverty levels in Aceh Province. Where the HDI affected negatively the level of poverty. Where it can be used as input for social and population policies of Aceh Province, namely the need to increase development that concentrates on HDI. In addition, it is necessary to know the level of inequality of HDI between regions in Aceh Province considering that HDI can affect the level of poverty.